2017
DOI: 10.2174/1574888x12666170523155846
|View full text |Cite
|
Sign up to set email alerts
|

From Stem Cell Biology to The Treatment of Lung Diseases

Abstract: Though not yet approved for clinical usage, the application of stem cell therapies shown to be safe and with minimal adverse effects could be an alternative treatment to many lung diseases giving a hope for the future of severely ill patients refractory to the current therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…During chemical injury of the lung, approximately 50% of the remaining BCs have shown club or ciliated cell markers; these BCs rapidly and directly differentiate into ciliated cells during repair, while club cells dedifferentiate into BCs, which function as stem cells for the long‐term maintenance of the tracheal epithelium 15,18,19 . Rare populations of BCs have been shown to have bronchiolar airway repair effects in mouse models, 20,21 such as p63 + Krt5 + BCs 7,16,22,23 and adult tracheobronchial tissue stem cells (TSCs)/progenitor cells 24,25 . A previous report demonstrated that intravenous transplantation of a human canalicular‐stage embryonic lung cell mixture into NOD‐SCID mice can give rise to chimeric lung tissue 26 .…”
Section: Discussionmentioning
confidence: 99%
“…During chemical injury of the lung, approximately 50% of the remaining BCs have shown club or ciliated cell markers; these BCs rapidly and directly differentiate into ciliated cells during repair, while club cells dedifferentiate into BCs, which function as stem cells for the long‐term maintenance of the tracheal epithelium 15,18,19 . Rare populations of BCs have been shown to have bronchiolar airway repair effects in mouse models, 20,21 such as p63 + Krt5 + BCs 7,16,22,23 and adult tracheobronchial tissue stem cells (TSCs)/progenitor cells 24,25 . A previous report demonstrated that intravenous transplantation of a human canalicular‐stage embryonic lung cell mixture into NOD‐SCID mice can give rise to chimeric lung tissue 26 .…”
Section: Discussionmentioning
confidence: 99%
“…CSCs contain the self-renewal abilities which are similar to the normal stem cells, targeting CSCs also can become an effective strategy to treat cancers. 113 Linc00662, a newly discovered LncRNA, had a strong correlation with lower overall survival rate and higher lymph node metastasis rate of patients with lung cancer. Lin28, as an RNA-binding protein and a reprogramming factor, can promote the tumourigenesis and progression in many human cancers.…”
Section: Influence the Properties Of Cancer Stem Cell (Csc)mentioning
confidence: 98%
“…Cancer stem cells (CSCs) play an important role in maintaining capacity of tumour metastasis, invasion and recurrence . Because CSCs contain the self‐renewal abilities which are similar to the normal stem cells, targeting CSCs also can become an effective strategy to treat cancers . Recently, some LncRNAs are discovered relating with the NSCLC metastasis via influencing the properties of CSCs.…”
Section: Main Regulating Manner Of Lncrnas To Influence the Metastasimentioning
confidence: 99%
“…This poor prognosis is due to metastasis in the late stage of disease. Cells with a stem‐like, dormant phenotype, endowed with unlimited self‐renewal and high tumorigenic capability, are deemed responsible for post‐therapy relapse and metastatic dissemination in various cancers, including lung cancer . Therefore, the drugs that attack the cancer stem cells (CSCs) population have therapeutic benefit.…”
Section: Introductionmentioning
confidence: 99%